York : art, architecture and archaeology - Brown, Sarah; Brown, Sarah; Rees Jones, Sarah; Rees Jones, Sarah; Ayers, Tim; Ayers, Tim (Conference transactions / British Archaeological Association, 2021)
The Shrines of St William of York Reconstructed / STUART HARRISON -- The Patronage of the Chapter-House in York Minster / HILARY MOXON -- The Chapter-House Roof of York Minster / JULIAN MUNBY -- York Minster at the time of the Black Death: the Stained Glass and Chantry-Chapel of Archbishop Zouche / CHRISTOPHER NORTON -- The Constructional Context of the Great East Window at York Minster / ALEXANDER HOLTON -- Looking for John Thornton: the Great East Window of York Minster Revisited / SARAH BROWN -- Archaeology and the Investigation of Vernacular Buildings in Late Medieval York / GARETH DEAN and JAYNE RIMMER -- Medieval Yorkshire Roads, Bridges and York Merchants / DAVID HARRISON -- The Early Sixteenth-Century Stained-Glass Programme of St Michael-le-Belfrey, York / LISA REILLY and MARY B. SHEPARD -- The Material World of the York Plays / RICHARD BEADLE.